Multilingual Education: A Catalyst for Professional Pathways (Journal of Asian Development Studies, 2024)
Pakistan faces challenges in balancing language policy, instructional practices, and sociocultural diversity to compete with the world. With over 7000 languages globally, Pakistan onlyfocuses on two languages: one national language, i.e. Urdu and then the official language,English. This research aims to analyze the impact of multilingual education on students' academicperformance, particularly for students in Pakistan, and its implications for future careerdirections. This research uses Cummins' Multilingual Education Framework as the theoreticallens in examining 40 participants, who are university students and teachers. The resultsdemonstrate the importance of the ongoing advocacy for languages and suggested policies foreffective MLE. Additional Chinese, German, Russian, and French languages are also shown tofurther career opportunities. Findings also reveal that 80% of the participants favored MultiLanguage Education as it is essential for career development and professional growth. The studyalso showed that multilingual education could improve students' cognitive skills, socialinteractions, and economic growth. Further, this research helps the emergence of multilingualeducation in Pakistan, which meets the needs of dual and multilingual students living in theglobalized world.